Cyber risk management disclosure: A stakeholder theory perspective - Siti Jubaedah; Agung Musta'in; Izza Nurlisti; Bayu Adam Maulana (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2024)
The purpose of this study was to examine the effect of ownership structure with sub-variables of management ownership, foreign ownership, dispersed ownership, and block ownership on cyber risk management disclosure. The research method uses quantitative methods with secondary data. The sample was 110 from 22 companies obtained through judgment sampling technique from annual reports and sustainability reporting. The population in this study are financial services sector companies listed on the Indonesia Stock Exchange from 2018-2022. The data analysis used is multiple linear regression. This study shows that there is a significant positive effect of foreign ownership and block ownership on cyber risk management disclosure but not significant for management ownership and dispersed ownership. This research may be a consideration for regulators to make investment policies and the government to make regulations that encourage companies to disclose cyber risk management reporting and can be a managerial concern for making policies and strategies in disclosing cyber risk management items.